Factors That Influence The Incident Of Retained Placenta Lanto Dg. Pasewang Hospital Jeneponto - Dwi Ghita Tahier; Nurrahma Layuk; Riska Reviana (Ammar Dharma Foundation, 2024)
Background: Retained placenta is one of the leading causes of postpartum hemorrhage, which can threaten the lives of mothers if not managed properly. This condition is a significant concern in efforts to reduce maternal mortality rates in Indonesia, especially in areas with limited healthcare facilities.Objective: This study aims to determine the factors influencing the incidence of retained placenta in maternity patients at Lanto Dg. Pasewang Hospital, Jeneponto.Research Method: This research employs a descriptive quantitative design. The study population includes all patients diagnosed with retained placenta at Lanto Dg. Pasewang Hospital, Jeneponto, from January to October 2022, totaling 50 individuals. The sampling technique used is purposive sampling. Data were collected from hospital medical records and analyzed using the chi-square test.Results: The results showed that age, birth interval, and the occurrence of anemia have significant relationships with the incidence of retained placenta. Most cases of retained placenta occurred in mothers aged over 35 years (39.5%), with birth intervals of 2-5 years (42.1%), and experiencing moderate anemia (39.4%).Conclusion: Older maternal age, shorter birth intervals, and the occurrence of anemia are significant risk factors for retained placenta. Proper management and early detection of these factors are crucial to prevent life-threatening postpartum hemorrhage.